Effect of Chi-alg Encapsulated 6% Curcumin Isolated from Mother Rhizome on Diabetes Mellitus in L6 Cell Lines - Swarnalatha, Y. (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: In this study, antidiabetic activity of 6% curcumin and chi-alg-encapsulated 6% curcumin isolated from the curumina longa (commonly called as turmeric) mother rhizome were evaluated and compared. Materials and Methods: The 6% curcumin-chi-alg encapsulated nanoparticles were prepared and characterized using scanning electron microscope and Fourier transform infrared. The antidiabetic activity of 6% curcumin was estimated in L6 cell lines. Cell viability was assessed using (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, and 3T3L1 antiadipogenesis assay was performed and in-vitro Î±-amylase activity was done. Results and Discussion: The chi-alg encapsulated curcumin found to possess the maximum antidiabetic activity. Encapsulated curcumin demonstrated better Î±-amylase inhibition activity than curcumin alone with inhibitory concentration 50% value of 36.81 Î¼g/ml. The encapsulated curcumin reduced the lipid accumulation in differentiated adipocytes. Increase in the 2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxy-D-glucose uptake by the cells cumulatively reflects the uptake of the glucose by encapsulated curcumin treatment. Conclusion: The current results suggest that the chi-alg encapsulated curucmin exhibit its antidiabetic activity by various types of mechanisms, including enhancing the glucose uptake by adipose tissue, suppresses the adipogenesis.